2022
DOI: 10.3389/fendo.2022.835033
|View full text |Cite
|
Sign up to set email alerts
|

A Synbiotic Combination of Lactobacillus gasseri 505 and Cudrania tricuspidata Leaf Extract Prevents Stress-Induced Testicular Dysfunction in Mice

Abstract: This study investigated the effects of a synbiotic combination (Syn) of Lactobacillus gasseri 505 (505) and Cudrania tricuspidata leaf extract (CT) on the hypothalamic-pituitary-gonadal axis in mice under chronic stress. Unpredictable chronic mild stress (UCMS) significantly increased the serum levels of corticosterone, however, treatment with Syn suppressed UCMS-induced increases. Histopathological analysis of the testes showed that these organs experienced some damage during UCMS, but this was repaired follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…The elevated level of Lactobacillus helps to increase the efficiency of energy metabolism for the host. In addition, bacteria from Lactobacillus can attenuate testicular dysfunction in male mice by affecting the secretion of hormones (e.g., GnRH) associated with the HPG axis [ 73 ], which is critical for regulating seasonal breeding behavior. Several studies have also shown that Lactobacillus can improve spermatogenesis and enhance sperm quality in animals [ 74 , 75 , 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…The elevated level of Lactobacillus helps to increase the efficiency of energy metabolism for the host. In addition, bacteria from Lactobacillus can attenuate testicular dysfunction in male mice by affecting the secretion of hormones (e.g., GnRH) associated with the HPG axis [ 73 ], which is critical for regulating seasonal breeding behavior. Several studies have also shown that Lactobacillus can improve spermatogenesis and enhance sperm quality in animals [ 74 , 75 , 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…Joung et al found that the probiotic L. gasseri 505 suppressed UCMS-induced corticosterone. Adding leaf extract Cudrania tricuspidata did not produce an additional effect on corticosterone [ 239 ]. In acute stress, Barrera-Bugueno et al showed that co-treatment with L. casei 54-2-33 and inulin in rats decreased the elevated plus maze-induced corticosterone [ 240 ].…”
Section: Introductionmentioning
confidence: 99%